Serum Sodium Concentration and Increased Risk for Primary Epiretinal Membrane - Xue, Can Can; Cui, Jing; Zhu, Xiao Bo; Xu, Jie; Zhang, Chun; Chen, Dong Ning; Wang, Ya Xing; Jonas, Jost B. (Frontiers in Medicine, 2021)
Abstract Aims: To examine the prevalence of primary epiretinal membranes (ERMs) and associated systemic factors. Methods: The cross-sectional, community-based Tongren Health Care Study enrolled participants who received regular health examinations in the Beijing Tongren Hospital from 2017 to 2019. Using fundus photographs, retinal specialists assessed the presence of ERMs and its systemic associations. Results: Primary ERMs were detected in 841/22980 individuals, with a prevalence of 3.7% (95% confidence intervals (CI):3.4-3.9%) in the total study population (mean age:44.5±13.8 years) and 6.5% (95%CI:6.1-7.0%) in individuals aged 40+ years. In multivariable analysis, a higher ERMs prevalence was associated with older age (odds ratio(OR):1.11; P<0.001), higher serum cholesterol concentration (OR:1.14; P=0.003) and higher serum sodium concentration (SSC) (OR:1.11; P<0.001). In women, a higher SSC, even within the normal range, was associated with increased odds of ERMs (OR:1.19; P<0.001). Female participants with an SSC of 144-145mmol/L as compared with those with an SSC of 135-137mmol/L had a 5-fold increased odds of having ERMs (All women: OR:5.33; P<0.001; Women aged 40+ years: OR:4.6; P<0.001). Conclusion: Our study suggests a higher SSC, even if within the normal range, was independently associated with a higher ERM prevalence in women, besides older age and higher serum cholesterol concentration.